STRATEGI GURU PADA PENINGKATAN KEMAMPUAN BERBICARA DALAM BAHASA BALI - Purnomo Arta, Putu Eddy; Riva Prathiwi, Kadek Jayanthi; Ruminten, I Kadek (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2021)
This research examines the teacher's strategy for increasing the ability to speak in Balinese. The method used is a qualitative method with a descriptive approach. The use of local languages in everyday life, especially Balinese, has declined due to lack of motivation to learn. This is reflected when speaking in Balinese. Seeing this phenomenon, then a teacher has an important role in improving students' speaking skills in accordance with the language of Bali. The purpose of this study is to improve students' speaking ability in Balinese. Through appropriate learning strategies, teachers are expected to be able to improve students' speaking skills, which are supported by the family environment. Factors that influence students' speaking skills using Balinese are internal and external factors. Hopefully, with the collaboration between family and teachers in schools in educatingÂ children, especiallyÂ practicing the ability to speak in Balinese, can give birth to a child who loves his own culture, especially Balinese.